Muse of fire : World War I as seen through the lives of the soldier poets - Korda, Michael, 1933- (Liveright Publishing Corporation, 2024)
With Muse of Fire, Michael Korda takes a novel approach to World War I by telling its history through the lives of the soldier-poets whose verses memorialize the war's unimaginable horrors. He begins with Rupert Brooke and the halcyon days before violence engulfed his generation--destroying the self-contented world of Edwardian England--and ends with the tragic death of Wilfred Owen, killed only days before the armistice brought an end to a war that took over 25,000,000 lives. Korda recounts these four years of a civilization destroying itself and portrays the lives and anguished deaths of the young men who unforgettably illuminated it. As the success of Pat Barker's Regeneration, the remake of All Quiet on the Western Front, and the images of brutal trench warfare in today's Ukraine demonstrate, contemporary interest in "the war to end war" remains high. --